PENGARUH FITOREMEDIASI Wolffia arrhiza TERHADAP KINERJA BUDIDAYA IKAN NILA (Oreochromis niloticus) - Anggi Soesalit; Mochammad Nurhudah; Sinung Rahardjo; Maria Goreti Eny Kristiany; Ai Setiadi (Universitas Mataram, 2026)
Water quality in fish farming significantly impacts the growth of the fish being farmed. Decreased air quality is caused by organic waste from uneaten feed and fish metabolites, largely dominated by nitrogen and phosphorus compounds. A solution to address the problem of improving air quality is phytoremediation (a wastewater treatment effort using plants). W. arrhiza is a potential phytoremediator. The aim of this study was to determine the effect of W. arrhiza phytoremediation on tilapia cultivation performance. This study employed a quantitative approach, using W. arrhiza as a test plant in varying amounts: P0 (control), P1 (50 g/m2), P2 (150 g/m2), and P3 (250 g/m2), with tilapia as the test fish. The study was conducted at the Fish Farmers Group Cing Mina Fish Farming Group Bogor Regency. The results of the study conducted for 30 days showed that the maintenance of tilapia with a phytoremediation system using W. arrhiza had a significant effect on the survival rate and feed conversion ratio (P<0.05), but had no significant effect on the growth of standard length, absolute weight growth and daily growth rate (P>0.05). Treatment P3 showed the highest values in the parameters of survival rate and feed conversion ratio with values of 94.17±0.76% and 1.3±0.09. While the absolute weight growth and absolute growth rate of the test plants had the highest values in treatment P1 with values of 834±97.68 g and 27.80±3.26 g.